SEG Technical Program Expanded Abstracts 2015 2015
DOI: 10.1190/segam2015-5831164.1
|View full text |Cite
|
Sign up to set email alerts
|

Prestack Seismic Inversion by Quantum Annealing: APPLICATION TO CANA FIELD

Abstract: The aim of seismic inversion is to estimate subsurface elastic properties. Deterministic seismic inversion based on local optimization suffers from becoming trapped in a local minimum. Also, the inversion result is generally band limited. Various stochastic inversion algorithms have been introduced to address these issues. Many of them, however, are computationally very expensive or can be trapped in a local minimum if the inversion parameters are not carefully chosen. Quantum Annealing (QA) is a global optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Global minimization techniques, such as simulated annealing, can be employed to find the global minimum. Previous numerical works [9,10] have indicated that it can be advantageous to use quantum annealing to solve seismic problems since, in the quantum approach, it is easy to escape from local minima due to tunneling effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global minimization techniques, such as simulated annealing, can be employed to find the global minimum. Previous numerical works [9,10] have indicated that it can be advantageous to use quantum annealing to solve seismic problems since, in the quantum approach, it is easy to escape from local minima due to tunneling effects.…”
Section: Discussionmentioning
confidence: 99%
“…In those works, it was shown that, although the size of the problem that can be solved on a third-generation D-Wave quantum annealer is considered small for moderns computers, they are larger than the problems solved with similar methodology with Intel's third and fourth generation chips. In references [9,10] it is demonstrated that a stochastic quantum annealing inversion of seismic data has superior performance over simulated annealing and deterministic inversion. However, the performance of the current available quantum computers has not yet been tested in seismic problems.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to mention that optimization techniques are widely used in seismic inversions, but usually classical algorithms get stuck in local minima. Previous works [13][14][15] have indicated that quantum annealing can be advantageous to solve seismic problems. However, the potential applications of quantum computing in Geoscience has so far been largely unexploited in the specialized literature.…”
mentioning
confidence: 99%